Incidence of breast carcinomas in male: a literature review (Research, Society and Development, 2022)
It is known that the subject of breast cancer is one of the most discussed and researched subjects, both for early detection and the search for a possibility of a treatment before a worsening of the pathology in the patient, but it is also considered that the search for treatment or even for routine medical consultation by men is very low, which leads to more severe health problems and most of the times identified late. In this sense, it is understood that with the late diagnosis of male breast cancer, the chances of treatment and consequently of cure become more difficult and challenging when compared to the same pathology faced by women. The objective of the work is to generate the same attention given to male breast cancer as is given to the same problem in females, it is a disease that has a treatment, but with the low number of men seeking exams and consultations, together with the lack of actions aimed at the early detection of this pathology in this genre, makes treatment very difficult, which in most cases, when detection happens, it is already in an advanced stage of the disease. The study was prepared through a bibliographic review, in the following databases: Scientific journals, SCIELO, Google Scholar, Ministry of Health website, and PUBMED, referring to the theme. Taking into account the research and results obtained, it was seen that breast carcinoma does not have as much visibility when mentioned in male patients, even though its incidence is relevant.